Surface localization of high-mobility group nucleosome-binding protein 2 (HMGN2) on leukemic B cells from chronic lymphocytic leukemia patients is related to secondary autoimmune hemolytic anemi - Morande, Pablo Elías (2015)
Chronic lymphocytic leukemia (CLL) is the main cause of autoimmune hemolytic anemia (AHA). However, the cellular basis underlying this strong association remains unclear. We previously demonstrated that leukemic B cells from patients with CLL recognize the erythrocyte protein Band 3, a prevalent autoantigen in AHA. Here we show that the major binding site of Band 3 on leukemic cells is an extrinsic protein identified as high-mobility group nucleosome binding protein 2 (HMGN2), a nucleosome-interacting factor which has not been previously reported at the cell surface. T lymphocytes do not express HMGN2 or bind Band 3. Removal of HMGN2 from the cell membrane abrogated the capacity of Band 3-pulsed CLL cells to induce CD4 + T cell proliferation. We conclude that surface HMGN2 in leukemic B cells is involved in Band 3 binding, uptake and presentation to CD4 + T lymphocytes, and as such may favor the initiation of AHA secondary to CLL.